Hak Petani atas Pemuliaan Tanaman Menelusuri Perlindungan Hukum di Indonesia dan Malaysia - Febrian Halomoan; Rildo Anuar Sihite; Wahidul Halim; Atik Winanti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
As an agricultural country, farmers in Indonesia have a crucial role, their existence must be safeguarded within the agricultural sector. Encouraging farmers to engage in breeding or develop new superior plant varieties is essential for fostering independent and advanced Indonesian farmers. These breeding activities are governed by Law Number 22 of 2019 on Sustainable Agricultural Cultivation System, and Law Number 29 of 2000 Plant Variety Protection. However, these laws have led to challenges for farmers involved in breeding, as the Plant Variety Protection Law adopts liberal approach that prioritizes individual economic benefits and specifically protects breeders who have registered their new varieties. As a result, farmers who use traditional knowledge in their breeding practices are vulnerable to criminalization due to the registration system. This paper will examine the rights of farmers in breeding activities under Indonesian law and compare with regulations in Malaysia, which shares geographical proximity, customs, and membership in the World Trade Organization. The research method is normative legal research, utilizing both conceptual and comparative approach. The objective to explore the legal protection of farmers’ rights in breeding activities in both Indonesia and Malaysia, and provide recommendations for improving the protection of farmers' rights in the future.